Molecular modeling and molecular dynamics simulation of the polarization switching phenomena in the ferroelectric polymers PVDF at the nanoscale - Bystrov, V. S.
The molecular modeling and molecular dynamics of polarization switching for the ferroclectric Earns model of polyvinylidene fluoride (PVDF) are investigated at the nanoscale. We consider a molecular model of PVDF film, consisting of two and four a chains [-CH2-CF2-](n) limited by n=6 elementary units. The first-principle approach is applied to the switching and kinetics of these models. Two types of behavior were established for PVDF chains: simultaneous and sequential rotation in high and low electric fields. Kinetics of sequential polarization switching shows a homogeneous critical behavior in the low electric field with a critical point at Landau-Ginzburg-Devonshire (LGD) coercive field E=E-C. This type of kinetics demonstrates a kink-like behavior for polarization solitary wave propagation. The simultaneous type of kinetics demonstrates the total domain-like polarization switching. corresponding to exponential behavior of switching Lime in high electric field as for bulk samples. Corresponding LGD intrinsic coercive field for a two-chain and four-chains model is E-C similar to 2.0 GV/m with revealing size effect. Obtained results show common quantum nature of PVDF chains switching phenomena the quantum interaction of the PVDE. molecular orbitals under applied electric field at the nanoscale level. The results obtained are compared with experimental data. (C) 2013 Elsevier B.V. All rights reserved.